Community structure of metazoan parasites of Trichiurus lepturus (Perciformes, Trichiuridae) from Ubatuba, Southwestern Atlantic Ocean,Brazil - Glauco Baptista Franco Bueno; Julio Cesar Cenci de Aguiar; Sonia Maria Cursino dos Santos (Acta Scientiarum. Biological Sciences, 2014)
This study aimed to evaluate the community structure of metazoan parasites of Trichiurus lepturus from Ubatuba, Brazil. Fifty fish were collected in February 2008. Our statistical approach consisted in evidencing the most interesting infrapopulations, in order to try to understand the relationship between the variables regulating them. This analysis was based on a Poisson generalized linear model (GLM) developed with selection of variables using the corrected Akaike Information Criterion (AICc) and AIC weight. Larvae of Anisakidae and Lecithochirium microstomum seems to play an important role on this host-parasite system and their abundances were influenced by the ontogenetic shift in feeding of the hosts. Changes in characteristics of hosts included a negative relationship between increased abundance of anisakids’ larvae and reduction in host weight. Gender biases were statistically consistent, but further long-term research is required to confirm them. Finally, we show the challenges that may be addressed in future research.